An ANALYSIS OF STUDENTS’ SPEAKING ABILITY IN RETELLING STORY ON DESCRIPTIVE TEXT AT THE SECOND GRADE STUDENTS OF SMP YLPI PEKANBARU - Idayani, Andi; Des Adean Fitri, (Perspektif Pendidikan dan Keguruan, 2021)
ABSTRACT The aims of this research was to know students' ability in speaking and to find out which aspects are the most dominant problems for the students at the second grade students of SMP YLPI Pekanbaru. The focused of this research was to analyze the students' problems in speaking based on five components of speaking which are pronunciation, grammar, vocabulary, fluency and comprehension. The design of this research was a qualitative research. This research was conducted at SMP YLPI Pekanbaru. The population of this research was the second-grade students at SMP YLPI Pekanbaru which consists of 54 students. The researchers chose class II.2 as a sample with the total number of the students were 28 students through purposive technique sampling. The researchers used speaking test as the instrument of research. This research conducted via Whatsapp by recording the students’ performances when retell descriptive text. Then the researcher transcribed the videos into scripts and asked raters to provide the scores. From the results of this study, the researcher found that the students' speaking ability in retelling story had the average score of 3 and categorized as a good level. The pronunciation component, the students’ mean score was 2.8 points, while grammar got 3.5 points. Following that, vocabulary component was 3.2 points, conversely on fluency, it was 2.7 points. The last, the students’ average score on the component of comprehension was 2.8 points. Finally, it can be concluded that the most dominant problem faced by students in speaking was the fluency component. Keyword: Students’ Speaking Ability, Retelling Story, Descriptive Text